Gender, Media and Voice: Communicative Injustice and Public Speech, Jilly Boyce Kay (2020). (1st April 2021) - Martin, Catherine
Review of: Gender, Media and Voice: Communicative Injustice and Public Speech, Jilly Boyce Kay (2020)Palgrave Macmillan: Cham, 193 pp., ISBN 978-3-030-47287-0, h/bk, 89.99, e-book, 69.99